ANALYSIS OF BASKETBALL GAME: RELATIONSHIP BETWEEN LIVE ACTIONS AND STOPPAGES IN DIFFERENT LEVELS OF COMPETITION - Hugo Salazar; Julen Castellano Paulis (Federación Extremeña de Balonmano; University of Extremadura, 2020)
The purpose of this study was to investigate durations of live-time actions (LA) and stoppages (ST) and to compare the distribution of durations among different levels of competition and quarters. LA and ST have been recorded during 21 official games in four different levels of competition: Under 16-years-old (Spanish U16), 3rd division competition (Spanish LEB), 1st division competition (Spanish ACB) and Euroleague (EUR). One-way analysis of variance, Cohen ́s d (d) were implement to interpret the magnitude of differences and a sequential analysis was also performed. 72.8% of all ST events lasted less than 44 s and only 1% were longer than 120 s. EUR level has longer ST durations compared with LEB (d=0.25) and U16 (d=0.36). Fourth quarter exhibit the longest durations of ST (d=-0.32) due to a higher number of time outs and free throws events. Sequential analysis showed how short durations of LA (<16 s) were followed by short durations of ST (<14 s), and long ones (>46 s) activated long periods of SP (>38 s). The practical application of these results should be considered for the design of game-based conditioning programs, especially by understanding the most demanding scenario, with applicability in different levels of basketball.